2021
DOI: 10.1186/s12958-021-00784-3
|View full text |Cite
|
Sign up to set email alerts
|

Should rescue ICSI be re-evaluated considering the deferred transfer of cryopreserved embryos in in-vitro fertilization cycles? A systematic review and meta-analysis

Abstract: Background Total fertilization failure represents a particularly frustrating condition for couples undergoing in vitro fertilization. With the aim of reducing the occurrence of total fertilization failure, intracytoplasmic sperm injection (ICSI) has become the first choice over conventional in vitro fertilization (IVF) procedures although evidence of improved results is still debated and its use in couples without male factor infertility is not recommended. Among the strategies potentially usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Despite its increasing utility, rescue ICSI continues to generate unsatisfactory clinical pregnancy (10%) and implantation rates (5%) (Paffoni et al 2021). These data reflect the findings of a recent meta-analysis of 22 original studies encompassing 1686 rescue-ICSI cycles with 12,945 inseminated oocytes (Paffoni et al 2021) and correlate well with observations that embryos originating from post-ovulatory aged oocytes are generally of poorer quality and exhibit delayed or impaired development during embryogenesis ) (Fig. 1).…”
Section: Reduced Embryo Quality and Developmental Potentialsupporting
confidence: 79%
See 2 more Smart Citations
“…Despite its increasing utility, rescue ICSI continues to generate unsatisfactory clinical pregnancy (10%) and implantation rates (5%) (Paffoni et al 2021). These data reflect the findings of a recent meta-analysis of 22 original studies encompassing 1686 rescue-ICSI cycles with 12,945 inseminated oocytes (Paffoni et al 2021) and correlate well with observations that embryos originating from post-ovulatory aged oocytes are generally of poorer quality and exhibit delayed or impaired development during embryogenesis ) (Fig. 1).…”
Section: Reduced Embryo Quality and Developmental Potentialsupporting
confidence: 79%
“…Further supporting this premise, clinical studies assessing the effects of in vivo post-ovulatory oocyte ageing have reported significant correlations with delayed fertilisation and early pregnancy loss (Wilcox et al 1998). The mechanisms underlying these low implantation and ensuing pregnancy rates have been attributed to time-and ROS-dependent deterioration in oocyte quality but may also be influenced by the loss of synchronisation between endometrial growth and embryo development (Paffoni et al 2021). The latter of these may allude to the evolutionary advantage of post-ovulatory ageing, whereby limiting the fertilisation of low-quality oocytes arising from desynchronisation of ovulation and insemination assists in avoiding complicated or ill-fated pregnancies and a possible wasted investment of resources.…”
Section: Reduced Embryo Quality and Developmental Potentialmentioning
confidence: 97%
See 1 more Smart Citation
“…Poor results were reported because of oocyte aging [ 3 ] and asynchronization between endometrial growth and embryo development [ 4 ]. Frozen embryo transfer seemed to improve with pregnancy rates (31–41%) and implantation rate (11–27%) [ 5 ], but it made no difference with fertilization. Subsequently, R-ICSI was performed earlier in an attempt to improve pregnancy rates since the 1990s [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A breakthrough in the field of r-ICSI cycles has recently come from the observation that good results can be achieved when r-ICSI embryos are transferred after cryopreservation in a subsequent frozen-thawed cycle [ 158 , 159 ]. A recent review by our group [ 160 ] including 22 original studies on late r-ICSI confirmed unsatisfactory results in fresh cycles with clinical pregnancy rate per embryo transfer and implantation rate equal to 10% and 5%, respectively. On the contrary, transfer of cryopreserved r-ICSI embryos was shown to ameliorate success rates, with pregnancy rate per embryo transfer equal to 37% with an odds ratio (OR) = 4.7 (95% CI: 2.6–8.5).…”
Section: Conventional Ivf and Fertilization Failurementioning
confidence: 99%